Exploring the Development of a User-Friendly Home Management System with ESP Rainmaker Firmware - Arowolo, Matthew Oluwole; Owolabi, Adekunle Okikioluwa; Bankole-Ajayi, Henry Onaopemipo; Akinyele, Oluwaseyi Paul (ABUAD Journal of Engineering Research and Development (AJERD), 2023)
With the rapid development of the Internet of Things (IoT), managing living spaces has become more intuitive than ever. This research illustrates the implementation of a user-friendly home management system utilizing the advanced ESP Rainmaker firmware from Espressif Systems. The study focuses on creating a seamless user experience through the efficient integration of ESP Rainmaker's features. Various hardware components are carefully selected to facilitate the creation of user-friendly smart devices, including intelligent lighting systems, switches, and climate control units. The specialized firmware tailored to the unique attributes of each device ensures secure connections with the ESP Rainmaker cloud services. The research delves into comprehensive provisioning techniques, including Bluetooth and SoftAP, to simplify device onboarding and ensure secure connectivity. Leveraging the Rainmaker cloud services, the system emphasizes the enhanced user control and synchronization of device states, contributing to an average success rate of 88% and an average response time of 2.1 seconds. This study provides valuable insights into the development of intuitive and secure home automation systems, underscoring the significance of integrated platforms like ESP Rainmaker in shaping the future of IoT-enabled living environments.